On the identification of cohesive zone model for curved crack in mortar. (6th July 2020) - Vargas, R.; Tsitova, A.; Bernachy‐Barbe, F.; Bary, B.; Canto, R. B.; Hild, F.
Abstract: This paper proposes an approach to defining the path of a curved crack in a single‐edge notched specimen with gray level residuals extracted from digital image correlation, followed by the calibration of the parameters of a cohesive zone model. Only the experimental force is used in the cost function minimized via finite element model updating. The displacement and gray level residual fields allow for the validation of the calibrated parameters. Last, the results are confronted with those given by a straight crack to highlight the benefits of accounting for the actual crack path.